Pest management for SCN bioassays and creation of new RNAI constructs for nematode suppression - Brady, Chad R. (Kansas State University, 2013)
The object of this study was to find a target sequence for the known Heterodera glycines Y25 sequence that contained no homology to any known Glycine max genes so homologous endogenous soybean gene expression will not be effected. In addition, in attempt to improve the accuracy of SCN bioassays performed in greenhouse settings, applications of a variety of insecticides with differing modes of action were applied to screen for any detectable effects on the SCN populations. The full-length sequence of the Y25 gene was blasted against the G. max genome using the National Center for Biotechnology Information blast database and a portion of the gene was found to contained no homology to the G. max genome. A rapid hairy root assay was used to screen for resistance to H. glycines. The sequence was transformed into Agrobacterium rhizogenes using a modified heat shock method. The transformed A. rhizogenes were used to inoculate soybean seedlings. The inoculated seedlings developed hairy roots expressing the target sequence. Upon finishing the hairy root assay it was discovered that there were no detectable differences across any of the treatments or the controls. It was neither proved nor disproved that the new target sequence containing no homology to the G. max genome was as effective as the original target. Further investigation will need to be conducted to show the level of control for the new target sequence.
Keywords: Ribonucleic acid interferance; Nematode; Heterodera glycines; Insecticide; Plant transformations; Soybean; Plant Pathology (0480); Plant Sciences (0479)